2017
DOI: 10.1099/jgv.0.000813
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus prevents excessive viral production via reduction of cell death-inducing DFF45-like effectors

Abstract: The relationship between hepatitis B virus (HBV) infection and lipid accumulation remains largely unknown. In this study, we investigated the effect of HBV propagation on lipid droplet growth in HBV-infected cells and HBV-producing cell lines, HepG2.2.15 and HBV-inducible Hep38.7-Tet. The amount of intracellular triglycerides was significantly reduced in HBV-infected and HBV-producing cells compared with HBV-lacking control cells. Electron and immunofluorescent microscopic analyses showed that the average size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Apart from reports that HBV increased lipogenesis, several other studies showed that HBV infection also increased fatty acid oxidation and reduced lipid droplets (LD) formation. Yasumoto et al (2017) showed that the content of intracellular TGs and the average size of a single LD were significantly reduced in HBV-infected or transfected cells compared to control cells, and that was because of decreased levels of proteins involved in LD expansionary and lipid storage. Studies also showed that HBV replication increased adiponectin expression (a downstream gene of PPARγ) (Yoon et al, 2011).…”
Section: Hbv-induced Changes In Fatty Acid Metabolismmentioning
confidence: 99%
“…Apart from reports that HBV increased lipogenesis, several other studies showed that HBV infection also increased fatty acid oxidation and reduced lipid droplets (LD) formation. Yasumoto et al (2017) showed that the content of intracellular TGs and the average size of a single LD were significantly reduced in HBV-infected or transfected cells compared to control cells, and that was because of decreased levels of proteins involved in LD expansionary and lipid storage. Studies also showed that HBV replication increased adiponectin expression (a downstream gene of PPARγ) (Yoon et al, 2011).…”
Section: Hbv-induced Changes In Fatty Acid Metabolismmentioning
confidence: 99%
“…Adiponectin protects against IR; thus, it is inversely associated with BMI, T2DM, and several metabolic disorders, such as cardiovascular disease and atherosclerosis [ 41 ]. Additionally, a study reported that HBV may influence lipid deposition and lipid droplet size in hepatocytes by decreasing the expression of cell death-inducing DFF45-like effectors (CIDEs) B and C (CIDEB and CIDEC), which are involved in lipid droplet expansion for improving lipid storage [ 42 ]. Thus, the increased risk and progression of both fatty liver and coronary disease should be carefully monitored when treating patients with chronic HBV and NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Yasumoto et al reported that CIDEB and CIDEC positively regulate cellular LD size. Overexpression of CIDEB or CIDEC enhanced HBV production in HBV-infected cells (HepG2.2.15), and deficiency in CIDEB or CIDEC impaired HBV production and reduced the size of single LDs [ 62 ]. Yasumoto et al also suggested that impairment of CIDE expression might stabilize an appropriate production level of HBV and inhibit excessive HBV productions [ 62 ].…”
Section: Hepatitis Viruses and Cholesterol Metabolismmentioning
confidence: 99%
“…Overexpression of CIDEB or CIDEC enhanced HBV production in HBV-infected cells (HepG2.2.15), and deficiency in CIDEB or CIDEC impaired HBV production and reduced the size of single LDs [ 62 ]. Yasumoto et al also suggested that impairment of CIDE expression might stabilize an appropriate production level of HBV and inhibit excessive HBV productions [ 62 ]. Experimental results from HBV-inducible Hep38.7-Tet cells incubated with HBV suggested that HBV production may affect the expression of CIDE proteins in hepatocytes, and CIDE proteins were found to significantly enhance the activity of HBV core promoter [ 62 ].…”
Section: Hepatitis Viruses and Cholesterol Metabolismmentioning
confidence: 99%